Sources of meaning in life among older adults during the COVID‐19 pandemic: A qualitative study - Chanhee Kim; Min Hye Lee; Kyung Im Kang (Wiley, 2023)
Abstract Aim This study aims to explore the sources of meaning in life (MIL) and its impact on South Korean older adults during the coronavirus disease 2019 (COVID‐19) pandemic. Design This study had a qualitative descriptive study design. Methods The study participants included 18 older adults. Six focus group interviews were conducted. Data were analysed using content analysis. Results The subcategories 'Continued learning and growth', 'Self‐transcending practices' and 'Efforts to maintain good health' were extracted under the category 'Sources of MIL for older adults'. Similarly, the subcategories 'Tremendous changes brought about by the virus' and 'Varying patterns of adjustment to the pandemic' were extracted under the category 'Changes in the sources of MIL since the COVID‐19 outbreak'. Public Contribution Our study provides an in‐depth understanding of the changed sources of MIL for older adults during the COVID‐19 pandemic. The findings serve as useful guidance for planning interventions for older adults to lead meaningful lives during the COVID‐19 pandemic and post‐pandemic crises.